Analysis of Differences in Chemical Constituents of Rougui Rock Tea with Different Roasting Degrees by Ultra-high Performance Liquid Chromatography-Quadrupole Orbitrap Mass Spectrometry - ZHONG Qiusheng, PENG Jiakun, DAI Weidong, LIN Zhi, LÜ Haipeng, CHEN Quanbin, LI Xinlei, CHEN Changsong (Shipin Kexue, 2023)
In order to investigate the influence of different roasting degrees on the quality and chemical composition of Rougui rock tea (Camellia sinensis (L.) O. Kuntze cv. Rougui), the non-volatile chemical compositions of tea samples processed at different roasting temperatures (low fire: 100 ℃, medium fire: 120 ℃, high fire: 140 ℃) and for different time periods (2, 4, 6, 8 and 10 h) were systematically investigated by metabolomics based on ultra-high performance liquid chromatography-quadrupole orbitrap mass spectrometry (UPLC-Q-Exactive/MS), and their quality was evaluated by sensory evaluation. A total of 144 compounds were structurally identified, belonging to 11 chemical classes including catechins, dimeric catechins, flavonoid glycosides (flavonol-O-glycosides and flavone-C-glycosides), N-ethyl-2-pyrrolidinone-substituted flavan-3-ols (EPSFs), amino acids, phenolic acids, organic acids, alkaloids, and lipids. Partial least squares discriminant (PLSD) analysis and heatmap analysis showed distinct differences in chemical components among rock tea samples with different baking treatments. A total of 84 compounds that significantly differed among treatment groups were identified (P < 0.05). The contents of most amino acids, epicatechins, dimeric catechins (theaflavins and theasinensins), alkaloids (5’-methionosine and adenosine phosphate), phenolic acids (isochlorogenic acid, strictinin and theogallin), and flavonoid glycosides were gradually decreased with roasting time at 120 ℃, while most lipids (MG(18:3), LysoPC(18:3), and palmitic acid), some flavonol aglycones (myricetin, kaempferol, and quercetin), and some organic acids (pyroglutamic acid and 5-hydroxymethyl-2-furfural) showed the opposite trend. The contents of most EPSF compounds were increased linearly with roasting temperature and time, but it was gradually decreased with baking time at 140 ℃. Sensory evaluation showed that low-temperature long-time (8–10 h at 100 ℃) and medium-temperature short-time (2–4 h at 120 ℃) were beneficial for the quality improvement of rock tea. This study provides a theoretical basis for the quality improvement of Wuyi rock tea.